Socio-philosophical analysis of education as the basis of the social and investment model of the strengthening of the statehood, social identity and elite of Kyrgyzstan - Aidaraliev, Amantur; Madaliev, Mukhtarbek M. (Frontiers in Education, 2025)
This paper seeks the goal of developing a newsocial and investmentmodel for strengthening statehood, social identity and the elite of Kyrgyzstan. Econometric modelling of the role of education in strengthening the statehood, social identity and elite of Kyrgyzstan based on the data of the official statistics for 2006-2021 is performed. As a result, a close connection between education and other interests in enhancing the statehood, social identity and elite of Kyrgyzstan is substantiated.The key role in this process belongs not to higher but to secondary vocational education. That is why it is set in the basis of the proposed social and investment model of strengthening of statehood, social identity and elite of Kyrgyzstan. The theoretical significance of the authors' conclusions is due to the most complete description of cause-and-effect relationships of enhancing the statehood, social identity and elite of Kyrgyzstan through the clarification of education's role in them.The social significance of the paper lies in the rethinking of the theory and practice of strengthening statehood, social identity and elite from the position of sustainable development. The authors' recommendations support the practical implementation of SDG 1, SDG 4, SDG 9, SDG 10 and SDG 11.